The Status and Role of Women in Sikh Religious Doctrine - Hermawan, Ucep; Huriani, Yeni; Hannah, Neng (UIN Sunan Gunung Djati Bandung, 2024)
This study explores the status and role of women within Sikh doctrine, aiming to contribute to and enrich academic discussions on the intersection of religious doctrine and gender studies. Using a qualitative approach that focuses on religion and gender, the research employs a library-based methodology, analyzing various sources and relevant prior studies. The findings demonstrate that women in Sikhism are granted equal status to men, rooted in the doctrine that emphasizes an intimate relationship between humans and the divine, where gender holds no significance in the connection to God. Moreover, the study delves into human relationships as shaped by behaviors, attitudes, and societal norms during the Sikh Gurus' era, illustrating the ideal dynamics between men and women. Despite Sikh teachings of equality, women in the Sikh community still face challenges in accessing leadership roles, as cultural and historical narratives often prioritize male dominance. The contributions of Sikh women have been historically marginalized, leaving subsequent generations with limited role models. This research offers both theoretical insights into Sikhism and gender and practical implications for encouraging the Sikh community, particularly men, to uphold Guru Nanak’s vision of gender equality.